2015
DOI: 10.1111/vop.12268
|View full text |Cite
|
Sign up to set email alerts
|

Tear ferning test in horses and its correlation with ocular surface evaluation

Abstract: Tear ferning test is easy to perform, without risks to the patient. Once standardized for horses, associated or not with the program STEPanizer(©) stereology tool, it is an additional method for evaluating the ocular surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 22 publications
2
29
1
1
Order By: Relevance
“…A larger volume of tear deposited on the slide, as, for example, would be the case with the use of glass rod, may also interfere with the phenomenon of crystallization . However, microcapillaries and micropipettes are the most common methods of tear collection for TFTs according to the medical literature, including in animals …”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…A larger volume of tear deposited on the slide, as, for example, would be the case with the use of glass rod, may also interfere with the phenomenon of crystallization . However, microcapillaries and micropipettes are the most common methods of tear collection for TFTs according to the medical literature, including in animals …”
Section: Discussioncontrasting
confidence: 76%
“…Thus, these factors were monitored to avoid environmental influences on crystallization. In the present study, we found a mean time of crystallization of 10 min, which is similar to that described in horses . Possible differences in tear composition could lead to a variation in the crystallization range, as well as in tear osmolarity, enabling dogs to show an increased range when compared to other species, besides having values greater than those obtained for humans .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tear ferning grading scales are based on previous studies with humans, and studies assessing TFTs in animals are scarce. 2,38,39 To compensate the absence of a specific scale and reference values, two grading scales were taken into account, the Rolando and Masmali scales. In this study, the operators observed differences in human and CM's tear film samples, as the crystal angulation and thickness, which could be attributed to variations in tear composition, sampling method, and temperature and environmental humidity.…”
Section: Descriptions Of Tear Osmolarity Have Previously Been Reportedmentioning
confidence: 99%